Perlindungan Hukum Ketenagakerjaan Terhadap Gig Worker Di Event Organizer Daerah Khusus Ibukota (DKI) Jakarta Selatan Pada Era Revolusi Industri 4.0 - Diadjeng Famelia Soerjadi; Abdullah Sulaiman; Diana Mutia Habibaty (JOURNAL of LEGAL RESEARCH, 2021)
The Gig Economy facilitates job seeker to look for job quickly. Job with contract system has become interesting since 2017, and it becomes the main job. However, the development of manpower sector is not the same line with the appropriate regulation in protecting the freelance workers especially in the Event Organizer sectors. The Event Organizer company often neglect the worker’s rights & obligations, since both parties don’t make working agreement writtenly. But they apply confidence principle each other in making working agreement orally. Since from the dominant number of Event Organizer in South Jakarta legally is choosen as the research object. This research is trying to focus on the people who want to work at certain time with Event Organizer sector to understand the importance of working agreement legally. This research is using judicial research method with qualitative analysis namely the data collection technique is based on library research and interview the freelance workers randomly in the field.